Impact of CEO compensation and CEO Power on Firms’ Innovation Moderating Role of Ownership Structure - Hamza Akram; Neelam Azam; Muhammad Usman Farooq; Abdul Ahad; Usama Saadat (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2022)
CEO compensation and power have crucial issues in assessing the innovative culture of firms. To address this issue, this study aims to investigate the nexus between CEO compensation and power on firms’ innovation under moderating role of ownership structure (measured in terms of ownership concentration, business group affiliation and CEO ownership). Ownership structure (ownership concentration, business group affiliation and CEO ownership) enables shareholders to exercise their statutory rights which play a vital role in the strategic decision-making of a company. To test the aforesaid relationship, data has been extracted from 27 chemicals and pharmaceutical firms listed at the Pakistan Stock Exchange during 2013-2021. The data gathered, thus, has been analyzed using various statistical techniques namely: descriptive analysis, correlation analysis, and multiple regression analysis. Due to presence of various issues in data such as heteroscedasticity, auto-correlation and cross-sectional dependence, researcher has employed Panel Corrected Standard Error Model (PCSE). The findings reveal that CEO compensation has positive effect on firms’ innovation. Another interesting finding is that this relationship becomes negative under conditional role of ownership structure (ownership structure, business group affiliation, and CEO ownership) which supports agency theory. However, CEO power has no role in firms’ innovation even under moderating role of ownership structure. The findings offer certain implications for practitioners to fix the compensation of CEO in order to resolve type I and II agency issues, which can improve firms’ innovation. Findings of this study can help investors, policymakers and creditors to understand the importance of CEO compensation and power towards firm innovation in the presence of ownership structure